Leber’s hereditary optic neuropathy: Update on current diagnosis and treatment - Esmaeil, Ali; Ali, Ali; Behbehani, Raed (Frontiers in Ophthalmology, 2023)
Leber’s hereditary optic neuropathy (LHON) is a fairly prevalent mitochondrial disorder (1:50,000) arising from the dysfunction of the mitochondrial respiratory chain, which eventually leads to apoptosis of retinal ganglion cells. The usual presentation is that of a young male with a sequential reduction in visual acuity. OCT has been used to study the pattern of optic nerve involvement in LHON, showing early thickening of the inferior and superior retinal nerve fibre layer and ganglion cell layer thinning corresponding with the onset of symptoms. Of the three primary mutations for LHON, the m.14484T>C mutation has the best visual prognosis. Recent emerging therapeutic options for LHON include idebenone and the introduction of genetic vector therapy, which is currently in phase III clinical trials. Screening of family members and adequate advice to avoid environmental triggers, such as smoking and alcohol consumption, are also cornerstones in the management of LHON.